Построение математической модели полного электромагнитного подвеса ротора с использованием взаимосвязанных магнитомеханических уравнений Рауса - Мартыненко, Геннадий Юрьевич (НТУ "ХПИ", 2007)
The method of the mathematical model creation for the full electromagnetic rotor bracket with controlled radial and axial electromagnetic bearings is offered. The design procedure of magnetic resistance for magnetic subcircuits is given. Namely, the eight-polar stators and pins on the rotor are proposed for the radial bearing, and the stator in the form of a cup core and shorting disk are proposed for the axial bearing.
Keywords: опоры роторов; электромагнитные подшипники; питающее напряжение; линеаризованные математические модели; центробежные компрессоры; наконечники статора